Model for asymptotic D-state parameters of light nuclei: Application to He4 - Adhikari, Sadhan K. [UNESP]; Frederico, T.; Goldman, I. D.; Sharma, S. Shelly (American Physical Society (APS), 1994)
A simple method for calculating the asymptotic D-state observables for light nuclei is suggested. The method exploits the dominant clusters of the light nuclei. The method is applied to calculate the He4 asymptotic D to S normalization ratio and the closely related D-state parameter D2. The study predicts a correlation between D2 and B, and between and B, where B is the binding energy of He4. The present study yields -0.14 and D2-0.12 fm2 consistent with the correct experimental d and the binding energies of the deuteron, triton, and the particle, where d is the deuteron D-state to S-state normalization ratio. © 1994 The American Physical Society.